Peningkatan Hasil Belajar Siswa Menggunakan Model Discovery Learning pada Pembelajaran Tematik Terpadu di Sekolah Dasar - Putra, Jimi Eka; Abidin, Zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
The study aims to describe the increased results of students’ learning at integrated thematic learning using the discovery learning models in class IV SDN 08 Koto Gadang Kecamatan IV Koto. This type of research is a class action study using qualitative and quantitative enatives. The subject of the study is IV class teacher as observers and twenty five students. Research shows that in observing the plan implementing learning on cycle I is 84,24% and cycle II 93,18%. The observed teacher activity on cycle I is 83,33% and cycle II 91,66%. The result of observation on student activity on cycle I is 81,94% and in cycle II 91,66%. The results of student study are one cycle with an average of 78,92 and on cycle two with and average of 85,06. Based on these results using the Discovery Learning model can improve the integrated thematic learning process in grade IV.